Charting a Path to Peace: Future Perspective for Human Rights from the Rise and Fall of Yugoslavia - Shen, Zhonghui (Mundus Slavicus I, 2025)
This article centers on the breakdown of Yugoslavia and how it can have implications for human rights implementation in multi-ethnic states. By analyzing case studies and historical contexts and making further references to the international intervention through the Dayton accord, the study elaborates upon the complexity of correlations with nationalism and universalism. It suggests that inclusive governance, thoughtful reconciliation, and education on human rights will avert another conflict while guaranteeing some semblance of peace.